Ion separation solar evaporator and preparation method thereof
Through the solar-powered ion separation solar evaporator, the nanofiltration membrane and multi-layer structure design of magnesium-lithium separation is used to achieve efficient and selective separation of Mg2+ and Li+ in salt lake water, solving the problems of high energy consumption and pretreatment in the existing technology, and realizing the direct collection of lithium salts, providing an environmentally friendly and economical lithium resource development solution.
Patent Information
- Application Number
- CN202510630326.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-06-13
AI Technical Summary
The existing technology has high energy consumption during the lithium extraction process of salt lakes, requires pretreatment of salt lake water, and cannot achieve direct collection of lithium salts, which limits the large-scale application of membrane separation technology in the development of lithium resources in salt lakes.
A solar-driven ion separation solar evaporator is used to achieve efficient selective separation of Mg2+ and Li+ through stacked transmission channels, ion separation layers, capillary layers and water evaporation zones. The device is made of two-dimensional layered material, composite surface plasmon material, rheology regulator and hydrogel. The ion separation layer uses a magnesium-lithium separation nanofiltration membrane.
It has achieved efficient and selective separation of Mg2+ and Li+ in salt lake brine, breaking through the high-energy bottleneck of the traditional nanofiltration membrane lithium extraction process, no need to pretreat the salt lake water, and can directly collect lithium-containing salts, simplifying the subsequent processing process, and providing an environmentally friendly, cost-effective solution for the development of lithium resources in salt lakes.
Smart Images

Figure CN120136220A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an ion separation solar evaporator and a preparation method thereof, belonging to the technical field of magnesium-lithium separation. Background Art
[0002] Compared with traditional Mg 2+ / Li + separation methods such as liquid-liquid extraction, adsorption, and electrodialysis, the nanofiltration membrane separation technology exhibits excellent separation performance for high-Mg 2+ / Li + brine due to its unique size sieving effect and Donnan equilibrium effect. However, the industrial application of nanofiltration membrane technology in lithium extraction from salt lakes still faces many challenges.
[0003] Firstly, when the nanofiltration membrane is used for lithium extraction from salt lakes, there is an inherent energy consumption in the separation process itself. Secondly, these membrane materials are usually difficult to directly treat high-salinity salt lake brines. If directly treating salt lake water, the operating pressure required to overcome the high osmotic pressure may exceed the mechanical strength limit of the nanofiltration membrane, and at the same time lead to a significant increase in energy consumption. Therefore, it is usually necessary to dilute and pretreat the salt lake water. Finally, the nanofiltration membrane separation can only obtain a low-concentration lithium-rich solution, and subsequent secondary concentration is still required through evaporation ponds or reverse osmosis and other technologies to meet the precipitation requirements of lithium products. This not only prolongs the process flow but also further increases the energy consumption. These technical bottlenecks restrict the large-scale application of membrane separation technology in the development of salt lake lithium resources. Therefore, there is an urgent need to develop a new salt lake lithium extraction process to achieve efficient Mg 2+ / Li + separation.
[0004] The existing solar evaporators combined with nanofiltration membranes disclosed in the prior art can extract lithium from salt water, but the salt water concentration and Li + flux that can be processed are relatively low, and the direct collection of lithium salts cannot be achieved.
[0005] Although the existing solar evaporators disclosed in the prior art can selectively extract lithium salts from salt water through nanofiltration membranes, the salts generated during their operation will continuously accumulate at the evaporation interface. If these deposited salts are not cleaned up in time, it will not only significantly reduce the evaporation rate but also affect the subsequent salt production.
[0006] The solar evaporator disclosed in the Chinese patent with the publication number CN117326615A can stably achieve water-salt co-production, but it cannot achieve selective separation of ions. Summary of the Invention
[0007] The purpose of the present invention is to provide an ion separation solar evaporator and a preparation method thereof, which can achieve Mg 2+and Li + for efficient and selective separation.
[0008] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides an ion separation solar evaporator, comprising a transmission channel, an ion separation layer, a capillary layer and a water evaporation zone stacked in sequence, and a salt crystallization zone is surrounded around the water evaporation zone; wherein, the transmission channel is made of a two-dimensional layered material, the water evaporation zone is made of a two-dimensional layered material composite surface plasmon material, the salt crystallization zone is made of a two-dimensional layered material composite rheology regulator, the capillary layer is made of a hydrogel, and the ion separation layer uses an ion separation nanofiltration membrane.
[0009] In combination with the first aspect, further, the transmission channel is made of reduced graphene oxide, the water evaporation zone is made of reduced graphene oxide composite titanium nitride, the salt crystallization zone is made of reduced graphene oxide composite poloxamer F127, the capillary layer is made of polyvinyl alcohol hydrogel, and the ion separation layer uses a magnesium-lithium separation nanofiltration membrane.
[0010] In combination with the first aspect, further, the transmission channel is a grid-shaped transmission channel, and the water evaporation zone is a grid-shaped water evaporation zone.
[0011] In a second aspect, the present invention provides a method for preparing an ion separation solar evaporator, comprising: Preparing a two-dimensional layered material ink, a two-dimensional layered material composite surface plasmon material ink and a two-dimensional layered material composite rheology regulator ink; 3D printing the transmission channel using the two-dimensional layered material ink, 3D printing the water evaporation zone using the two-dimensional layered material composite surface plasmon material ink, and 3D printing the salt crystallization zone using the two-dimensional layered material composite rheology regulator ink; Preparing a hydrogel and using the hydrogel to prepare the capillary layer; Preparing an ion separation nanofiltration membrane and using the ion separation nanofiltration membrane as the ion separation layer; Placing the ion separation layer, the capillary layer and the water evaporation zone on the transmission channel in sequence, and surrounding the salt crystallization zone around the water evaporation zone to obtain the ion separation solar evaporator.
[0012] In combination with the second aspect, further, the two-dimensional layered material ink is a reduced graphene oxide ink, the two-dimensional layered material composite surface plasmon material ink is a reduced graphene oxide composite titanium nitride ink, and the two-dimensional layered material composite rheology regulator ink is a reduced graphene oxide composite poloxamer F127 ink; Preparing the reduced graphene oxide ink, the reduced graphene oxide composite titanium nitride ink and the reduced graphene oxide composite poloxamer F127 ink includes: Stir the graphite flakes in a mixed acid of nitric acid and sulfuric acid. After dilution, filtration by suction, and drying, perform heat treatment to obtain a heat-treated product; React the heat-treated product with sulfuric acid, phosphorus pentoxide, and potassium persulfate. After washing and drying, obtain an intermediate product; React the intermediate product with sulfuric acid and potassium permanganate, and reduce the residual potassium permanganate. After centrifugal washing, add water to obtain an aqueous solution of graphene oxide; Add an ascorbic acid solution to the aqueous solution of graphene oxide for reaction, and perform filtration by suction on the reacted solution to obtain a reduced graphene oxide ink; Incorporate titanium nitride nanoparticles into the reduced graphene oxide ink to obtain a reduced graphene oxide composite titanium nitride ink; Mix the reduced graphene oxide ink with an aqueous solution of poloxamer F127 to obtain a reduced graphene oxide composite poloxamer F127 ink.
[0013] In combination with the second aspect, further, use the two-dimensional layered material ink to 3D print the transport channel, use the two-dimensional layered material composite surface plasmon material ink to 3D print the water evaporation area, and use the two-dimensional layered material composite rheology regulator ink to 3D print the salt crystallization area, including: Perform freeze-setting, vacuum drying, annealing, and oxygen plasma treatment on the 3D printed transport channel, water evaporation area, and salt crystallization area; Among them, the transport channel is a grid-like transport channel, and the water evaporation area is a grid-like water evaporation area; Mix each ink evenly when in use.
[0014] In combination with the second aspect, further, the hydrogel is a polyvinyl alcohol hydrogel; Prepare a polyvinyl alcohol hydrogel and use the polyvinyl alcohol hydrogel to prepare a capillary layer, including: Evenly mix an aqueous solution of polyvinyl alcohol and a glutaraldehyde solution to obtain a mixed solution; Add a hydrochloric acid solution to the mixed solution to initiate a cross-linking reaction and perform gelation to obtain a polyvinyl alcohol hydrogel; Remove the unreacted impurities in the polyvinyl alcohol hydrogel to obtain a pure polyvinyl alcohol hydrogel; Perform freeze-thaw treatment on the pure polyvinyl alcohol hydrogel and perform drying treatment to obtain a capillary layer.
[0015] In combination with the second aspect, further, the ion separation nanofiltration membrane is a magnesium-lithium separation nanofiltration membrane; Prepare a magnesium-lithium separation nanofiltration membrane, including: Disperse single-walled carbon nanotubes and sodium dodecyl sulfate into deionized water. After centrifugal purification, modify them with dopamine hydrochloride and add tris(hydroxymethyl)aminomethane buffer solution for reaction to obtain a dopamine hydrochloride / single-walled carbon nanotube dispersion; Filter the dopamine hydrochloride / single-walled carbon nanotube dispersion onto a polyethersulfone membrane to form a substrate membrane. After drying, immerse it successively in an aqueous solution of piperazine with sodium dodecyl sulfate and a n-hexane solution of trimesoyl chloride for interfacial polymerization. After rinsing with n-hexane and heat treatment, a magnesium-lithium separation nanofiltration membrane is obtained.
[0016] Thirdly, the present invention provides an application of an ion separation solar evaporator prepared by the method as described in any item of the first aspect or an ion separation solar evaporator prepared by the method as described in any item of the second aspect in lithium extraction from salt lakes.
[0017] Fourthly, the present invention provides a method for lithium extraction from salt lakes. Place an ion separation solar evaporator prepared by the method as described in any item of the first aspect or an ion separation solar evaporator prepared by the method as described in any item of the second aspect in salt lake water, and enable ions to selectively pass through the ion separation layer for lithium resource extraction.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: The ion separation solar evaporator provided by the present invention realizes efficient and selective separation of Mg 2+ and Li + in salt lake brine through a nanofiltration membrane separation technology driven by solar energy, breaking through the high energy consumption bottleneck of the traditional lithium extraction process based on nanofiltration membranes, and without the need for pretreatment of salt lake brine. In addition, lithium-containing salts can be directly collected, greatly simplifying the subsequent treatment process, and providing an environmentally friendly, economical and efficient solution for the development of salt lake lithium resources.
[0019] The ion separation solar evaporator provided by the present invention uses green energy solar energy for magnesium-lithium separation, realizing zero-energy consumption operation, and having significant low-cost and environmental protection advantages.
[0020] The ion separation solar evaporator provided by the present invention has excellent magnesium-lithium separation performance for high Mg 2+ / Li + ratio and high-concentration brine. Under the light intensity of 1 kW·m -2 , the separation factor of the ion separation solar evaporator for brine with an Mg 2+ / Li + ratio of 80 is as high as 21.68, while the Li -1 flux for brine with a concentration of 100 g·L + is as high as 0.486 g·m -2 ·h -1, and can increase Li with the increase of light intensity + flux, and its magnesium-lithium separation ability is higher than that of existing magnesium-lithium separation evaporators.
[0021] The ion separation solar evaporator provided by the present invention omits the pretreatment steps necessary for traditional processes, and the ion separation solar evaporator can directly produce lithium-containing salts, simplifies the process of extracting lithium from salt lakes, and reduces the operating cost. Description of the Drawings
[0022] Figure 1 is a schematic structural diagram of the ion separation solar evaporator provided by an embodiment of the present invention; Figure 2 is an SEM image of the water evaporation area at different magnifications provided by an embodiment of the present invention; Figure 3 is a schematic diagram of the composition characterization of the water evaporation area provided by an embodiment of the present invention, where (a) is the XRD pattern of the water evaporation area, and (b) is the light absorption rate of the water evaporation area in the wet state; Figure 4 is an SEM image of the salt crystallization area at different magnifications provided by an embodiment of the present invention; Figure 5 is an SEM image of the capillary layer at different magnifications provided by an embodiment of the present invention; Figure 6 is a schematic diagram of the microscopic morphology characterization of the magnesium-lithium separation nanofiltration membrane of the ion separation solar evaporator provided by an embodiment of the present invention; Figure 7 is a schematic diagram of the salt production of the ion separation solar evaporator provided by an embodiment of the present invention. Detailed Embodiments
[0023] The technical solutions of the present application will be further described in detail below in conjunction with the specific embodiments.
[0024] The embodiments of the present application will be described in detail below. The examples of the embodiments are shown in the drawings, where the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions from beginning to end. The embodiments described below by referring to the drawings are exemplary and are only used to explain the present application and should not be construed as limiting the present application. Without conflict, the embodiments of the present application and the technical features in the embodiments can be combined with each other.
[0025] An embodiment of the present application provides an ion separation solar evaporator, as Figure 1 shown, including a transmission channel, an ion separation layer, a capillary layer, and a water evaporation area stacked in sequence, and a salt crystallization area surrounds the water evaporation area.
[0026] In this embodiment, the transmission channel is made of a two-dimensional layered material, the water evaporation region is made of a two-dimensional layered material composite with a surface plasmon material, the salt crystallization region is made of a two-dimensional layered material composite with a rheology modifier, the capillary layer is made of a hydrogel, and the ion separation layer uses an ion separation nanofiltration membrane.
[0027] The ion separation solar evaporator provided by the embodiment of the present application adopts a modular multi-layer structure design, and each functional component is assembled between layers through the surface tension of water, and finally an ion separation solar evaporator is formed.
[0028] In a possible embodiment, the transmission channel is made of reduced graphene oxide, the water evaporation region is made of reduced graphene oxide composite with titanium nitride, the salt crystallization region is made of reduced graphene oxide composite with poloxamer F127, the capillary layer is made of polyvinyl alcohol hydrogel, and the ion separation layer uses a magnesium-lithium separation nanofiltration membrane.
[0029] In a possible embodiment, the transmission channel is a grid-shaped transmission channel, and the water evaporation region is a grid-shaped water evaporation region.
[0030] The embodiment of the present application provides a method for preparing an ion separation solar evaporator, including: Preparing a two-dimensional layered material ink, a two-dimensional layered material composite with a surface plasmon material ink, and a two-dimensional layered material composite with a rheology modifier ink; 3D printing the transmission channel using the two-dimensional layered material ink, 3D printing the water evaporation region using the two-dimensional layered material composite with a surface plasmon material ink, and 3D printing the salt crystallization region using the two-dimensional layered material composite with a rheology modifier ink; Preparing a hydrogel and using the hydrogel to prepare the capillary layer; Preparing an ion separation nanofiltration membrane and using the ion separation nanofiltration membrane as the ion separation layer; Placing the ion separation layer, the capillary layer, and the water evaporation region on the transmission channel in sequence, and surrounding the salt crystallization region around the water evaporation region to obtain an ion separation solar evaporator.
[0031] In a possible embodiment, the two-dimensional layered material ink is a reduced graphene oxide ink, the two-dimensional layered material composite with a surface plasmon material ink is a reduced graphene oxide composite with titanium nitride ink, and the two-dimensional layered material composite with a rheology modifier ink is a reduced graphene oxide composite with poloxamer F127 ink.
[0032] In this embodiment, preparing the reduced graphene oxide ink, the reduced graphene oxide composite with titanium nitride ink, and the reduced graphene oxide composite with poloxamer F127 ink includes: Stirring graphite flakes in a mixed acid of nitric acid and sulfuric acid, performing dilution, filtration, and drying, and then performing heat treatment to obtain a heat treatment product; React the heat-treated product with sulfuric acid, phosphorus pentoxide, and potassium persulfate. After washing and drying, an intermediate product is obtained. React the intermediate product with sulfuric acid and potassium permanganate, and reduce the residual potassium permanganate. After centrifugal washing, add water to obtain an aqueous solution of graphene oxide. Add ascorbic acid solution to the aqueous solution of graphene oxide for reaction, and perform suction filtration on the reacted solution to obtain reduced graphene oxide ink. Incorporate titanium nitride nanoparticles into the reduced graphene oxide ink to obtain reduced graphene oxide composite titanium nitride ink. Mix the reduced graphene oxide ink with an aqueous solution of poloxamer F127 to obtain reduced graphene oxide composite poloxamer F127 ink.
[0033] Specifically, the preparation of reduced graphene oxide ink includes the following steps: Step 1: Stir 1 g of graphite flakes in a mixed acid of 10 mL of concentrated nitric acid with a concentration of 68 wt% and 30 mL of concentrated sulfuric acid with a concentration of 98 wt% at room temperature for 24 h. After dilution, suction filtration, and drying, perform heat treatment at 1000 °C to obtain a heat-treated product. Step 2: Take 1 g of the heat-treated product and react it with 60 mL of concentrated sulfuric acid with a concentration of 98 wt%, 1.24 g of phosphorus pentoxide, and 0.84 g of potassium persulfate at 80 °C for 5 h. After washing and drying, an intermediate product is obtained. Step 3: Take 1 g of the intermediate product and react it with 30 mL of concentrated sulfuric acid with a concentration of 98 wt% and 3 g of potassium permanganate at 35 °C for 2 h, and add hydrogen peroxide to reduce the residual potassium permanganate. After centrifugal washing, add water to obtain an aqueous solution of graphene oxide. Step 4: Add ascorbic acid solution with a concentration of 80 mg·mL -1 to the aqueous solution of graphene oxide, react in an oven at 70 °C for 30 min, and perform suction filtration on the reacted solution to filter out most of the water to obtain reduced graphene oxide ink.
[0034] After obtaining the reduced graphene oxide ink, incorporate titanium nitride nanoparticles into the reduced graphene oxide ink to obtain reduced graphene oxide composite titanium nitride ink.
[0035] Specifically, the mass ratio of the solid content of titanium nitride nanoparticles to the reduced graphene oxide ink is 1:5 to 1:1.
[0036] Among them, the method for measuring the solid content of the reduced graphene oxide ink is as follows: Take a certain amount of the reduced graphene oxide ink sample and dry it in an oven. By calculating the ratio of the mass of the dried sample to the mass of the sample before drying, the solid content of the reduced graphene oxide ink can be determined.
[0037] After obtaining the reduced graphene oxide ink, the reduced graphene oxide ink is mixed with an aqueous solution of poloxamer F127 to obtain a reduced graphene oxide composite poloxamer F127 ink.
[0038] Specifically, the concentration of the aqueous solution of poloxamer F127 is 25 wt% to 50 wt%, and the mass ratio of the reduced graphene oxide ink to the aqueous solution of poloxamer F127 is 1:1 to 4:1.
[0039] In this example, the mass ratio of titanium nitride nanoparticles to the solid content of the reduced graphene oxide ink is 1:2.5, and the mass ratio of the reduced graphene oxide ink to the aqueous solution of poloxamer F127 is 2:1.
[0040] In a possible example, a two-dimensional layered material ink is used to 3D print a transport channel, a two-dimensional layered material composite surface plasmon material ink is used to 3D print a water evaporation area, and a two-dimensional layered material composite rheology modifier ink is used to 3D print a salt crystallization area, including: freeze-setting, vacuum drying, annealing, and oxygen plasma treatment of the 3D printed transport channel, water evaporation area, and salt crystallization area.
[0041] Specifically, the 3D printing is based on a modified industrial-grade 3D printing system, which has three-dimensional (x-axis, y-axis, z-axis) programmable patterning capabilities.
[0042] Before 3D printing, the inks to be used are mixed evenly using a homogenizer.
[0043] During 3D printing, a high-precision pressure controller (150 kPa to 300 kPa) and a precision needle with a diameter of 300 μm to 600 μm are used to perform patterning printing at a speed of 20 mm·s -1 ~50 mm·s -1 at room temperature.
[0044] After 3D printing, the sample (the 3D printed transport channel, water evaporation area, and salt crystallization area) is first frozen at -80°C for 2 h to fix the structure, and then subjected to 24 h of vacuum drying; then, under nitrogen protection, it is heated to 200°C at a heating rate of 1°C·min -1 and held for 30 min for annealing treatment; finally, oxygen plasma treatment is performed for 10 min to improve its hydrophilicity.
[0045] In a possible example, the transport channel is a grid-shaped transport channel, and the water evaporation area is a grid-shaped water evaporation area.
[0046] Specifically, a grid-shaped transport channel is 3D printed using a two-dimensional layered material ink, a grid-shaped water evaporation area is 3D printed using a two-dimensional layered material composite surface plasmon material ink, and a salt crystallization area is 3D printed using a two-dimensional layered material composite rheology modifier ink. Then, the 3D printed grid-shaped transport channel, grid-shaped water evaporation area, and salt crystallization area are subjected to freeze setting, vacuum drying, annealing, and oxygen plasma treatment.
[0047] In a possible embodiment, the hydrogel is a polyvinyl alcohol hydrogel.
[0048] In this embodiment, preparing a polyvinyl alcohol hydrogel and using the polyvinyl alcohol hydrogel to prepare a capillary layer includes: Uniformly mixing a polyvinyl alcohol aqueous solution and a glutaraldehyde solution to obtain a mixed solution; Adding a hydrochloric acid solution to the mixed solution to initiate a cross-linking reaction and carry out gelation to obtain a polyvinyl alcohol hydrogel; Removing unreacted impurities in the polyvinyl alcohol hydrogel to obtain a pure polyvinyl alcohol hydrogel; Performing a freeze-thaw treatment on the pure polyvinyl alcohol hydrogel and then performing a drying treatment to obtain a capillary layer.
[0049] Specifically, preparing a polyvinyl alcohol hydrogel and using the polyvinyl alcohol hydrogel to prepare a capillary layer includes the following steps: Step 1: Uniformly mix 5 g to 10 g of a polyvinyl alcohol aqueous solution with a concentration of 5 wt% to 15 wt% and 100 μL to 200 μL of a glutaraldehyde solution with a concentration of 50 wt% by ultrasonic treatment to obtain a mixed solution; Step 2: Add 40 μL to 60 μL of a hydrochloric acid solution with a concentration of 1 M to 3 M to 1 mL of the mixed solution to initiate a cross-linking reaction and carry out gelation at room temperature to obtain a polyvinyl alcohol hydrogel; Step 3: Immerse the polyvinyl alcohol hydrogel in deionized water to remove unreacted impurities to obtain a pure polyvinyl alcohol hydrogel; Step 4: Repeat the freeze-thaw treatment on the pure polyvinyl alcohol hydrogel 10 times and place it in a vacuum dryer for drying for 24 h to obtain a capillary layer.
[0050] In this embodiment, 7.5 g of a polyvinyl alcohol aqueous solution with a concentration of 10 wt% is uniformly mixed with 150 μL of a glutaraldehyde solution with a concentration of 50 wt% by ultrasonic treatment to obtain a mixed solution. Then, 50 μL of a hydrochloric acid solution with a concentration of 2 M is added to 1 mL of the mixed solution to initiate a cross-linking reaction and carry out gelation at room temperature to obtain a polyvinyl alcohol hydrogel.
[0051] In a possible embodiment, the ion separation nanofiltration membrane is a magnesium-lithium separation nanofiltration membrane.
[0052] In this embodiment, the preparation of the magnesium-lithium separation nanofiltration membrane includes: Disperse single-walled carbon nanotubes and sodium dodecyl sulfate into deionized water. After centrifugal purification, modify them with dopamine hydrochloride and add tris(hydroxymethyl)aminomethane buffer solution for reaction to obtain a dopamine hydrochloride / single-walled carbon nanotube dispersion; Filter the dopamine hydrochloride / single-walled carbon nanotube dispersion onto a polyethersulfone membrane to form a substrate membrane. After drying, immerse it successively in an aqueous piperazine solution containing sodium dodecyl sulfate and a 1,3,5-benzenetricarbonyl chloride n-hexane solution for interfacial polymerization. After rinsing with n-hexane and heat treatment, a magnesium-lithium separation nanofiltration membrane is obtained.
[0053] Specifically, the preparation of the magnesium-lithium separation nanofiltration membrane includes the following steps: Step 1: Ultrasonically disperse 20 mg to 50 mg of single-walled carbon nanotubes and 200 mg to 500 mg of sodium dodecyl sulfate into 400 mL of deionized water. After centrifugal purification, modify them with 20 mg to 50 mg of dopamine hydrochloride and add 10 mL to 20 mL of tris(hydroxymethyl)aminomethane buffer solution with a concentration of 0.08 mol·mL -1 ~0.12 mol·mL -1 for reaction for 40 hours to 60 hours to obtain a dopamine hydrochloride / single-walled carbon nanotube dispersion; Step 2: Filter the dopamine hydrochloride / single-walled carbon nanotube dispersion onto a polyethersulfone membrane to form a substrate membrane. After drying, first immerse it in an aqueous piperazine solution with a concentration of 8 mg·mL -1 ~12 mg·mL -1 The aqueous piperazine solution also contains sodium dodecyl sulfate with a concentration of 1 mg·mL -1 ~3 mg·mL -1 Subsequently, immerse it in a 1,3,5-benzenetricarbonyl chloride n-hexane solution with a concentration of 1 mg·mL -1 ~2 mg·mL -1 for interfacial polymerization. After rinsing with n-hexane and heat treatment for 60 s to 120 s, a magnesium-lithium separation nanofiltration membrane is obtained and stored refrigerated at 4 °C.
[0054] In this embodiment, 35 mg of single-walled carbon nanotubes and 350 mg of sodium dodecyl sulfate are ultrasonically dispersed into 400 mL of deionized water. After centrifugal purification, they are modified with 35 mg of dopamine hydrochloride and 15 mL of tris(hydroxymethyl)aminomethane buffer solution with a concentration of 0.1 mol·mL -1 is added for reaction for 50 hours to obtain a dopamine hydrochloride / single-walled carbon nanotube dispersion. The dopamine hydrochloride / single-walled carbon nanotube dispersion is filtered onto a polyethersulfone membrane to form a substrate membrane. After drying, it is first immersed in an aqueous piperazine solution with a concentration of 10 mg·mL -1 The aqueous piperazine solution also contains sodium dodecyl sulfate with a concentration of 2 mg·mL -1Sodium dodecyl sulfate, and then immersed in a solution of trimesoyl chloride in n-hexane with a concentration of 1.5 mg·mL -1 to carry out interfacial polymerization. After rinsing with n-hexane and heat treatment at 50 °C for 90 s, a magnesium-lithium separation nanofiltration membrane was obtained and stored at 4 °C.
[0055] The embodiment of the present application also provides a method for testing the salt production rate of an ion separation solar evaporator: Put the salt produced by the ion separation solar evaporator into an oven for drying. The mass of the salt after complete drying is , with the unit of kg.
[0056] The calculation formula for the salt production rate is: ; where represents the salt production rate, with the unit of kg·m -2 ·h -1 , represents the projected area of the ion separation solar evaporator, with the unit of m 2 , represents the test time, with the unit of h.
[0057] The embodiment of the present application also provides a method for testing the water transport performance of an ion separation solar evaporator: To facilitate the test of water transport performance, the test sample was printed into a three-dimensional grid structure using rGO / TiN ink and rGO-F127 ink. The height of the sample was 0.9 cm. After covering the surface of the sample with dust-free paper, it was immersed in a rhodamine B solution, and the water transport performance was characterized by observing the color change of the dust-free paper.
[0058] The embodiment of the present application also provides a method for testing the ion transport flux of an ion separation solar evaporator: Uniformly sprinkle NaCl on a dry ion separation solar evaporator with a projected area of (m 2 ), and then place it in a test solution with a salinity of (wt%). The concentration gradient formed at the evaporation interface promotes the diffusion of NaCl into the test solution. After the test time (h), measure the mass (kg) and salinity (wt%) of the test solution after the test. The ion transport flux (kg·m -2 ·h -1 ) of the ion separation solar evaporator is calculated by the formula: .
[0059] In the test, it is 3.5 wt%, and it is 5 min.
[0060] The embodiment of the present application also provides a method for testing the magnesium-lithium separation performance of an ion separation solar evaporator: Use the ion separation solar evaporator to determine the magnesium-lithium separation performance at different Mg 2+ / Li + ratios, in different concentrations of salt water, and under different light intensities. After each test, immerse the water evaporation area and the salt crystallization area of the ion separation solar evaporator in a hydrochloric acid solution with a concentration of 0.5 M, and ultrasonically treat for 2 h at room temperature to fully elute the adsorbed ions, and collect the obtained filtrate. Use inductively coupled plasma emission spectrometry to determine the concentrations of Li + and Mg 2+ in the filtrate.
[0061] The separation factor of the ion separation solar evaporator is calculated by the formula: ; where, , represent the concentrations of Mg 2+ , Li + in the original solution, , represent the concentrations of Mg 2+ , Li + in the obtained filtrate, and the unit is g·L -1 .
[0062] The Li + flux (kg·m -2 ·h -1 ) of the ion separation solar evaporator is calculated by the formula: ; where, represents the volume of the obtained filtrate, and the unit is L.
[0063] Characterize the ion separation solar evaporator prepared by the method for preparing an ion separation solar evaporator provided in the embodiment of the present application.
[0064] First, use a scanning electron microscope (SEM) to characterize the surface morphology of the water evaporation area of the ion separation solar evaporator. As shown in Figure 2 (a) and Figure 2As shown in (b), the water evaporation area prepared by 3D printing with reduced graphene oxide composite titanium nitride ink exhibits a significantly macroporous structure. The high-magnification SEM image shows that titanium nitride (TiN) nanoparticles are uniformly dispersed and attached to the surface of reduced graphene oxide (rGO) sheets.
[0065] Secondly, X-ray diffraction (XRD) was used to characterize the composition of the water evaporation area of the ion separation solar evaporator. As Figure 3 shown in (a), the XRD pattern shows that the characteristic diffraction peaks of rGO are retained in the water evaporation area, and at the same time, new diffraction peaks appear. These diffraction peaks are consistent with the PDF standard card of TiN (#38-1420), confirming the successful introduction of TiN nanoparticles into rGO. In addition, as Figure 3 shown in (b), due to the surface plasmon effect of TiN nanoparticles and the unique light-trapping structure of the water evaporation area, which enhances the capture of incident light, the average light absorption rate of the water evaporation area reaches 98.28%.
[0066] Next, SEM was used to characterize the surface morphology of the salt crystallization area of the ion separation solar evaporator. As Figure 4 shown in (a) and Figure 4 shown in (b), the salt crystallization area prepared based on reduced graphene oxide composite poloxamer F127 (rGO-F127) ink has an obvious microporous structure.
[0067] Subsequently, to explore the water-salt co-production mechanism of the ion separation solar evaporator, the water transport and ion transport properties of the water evaporation area and salt crystallization area of the ion separation solar evaporator were tested.
[0068] As shown in Table 1, the water transport rate of the sample prepared based on reduced graphene oxide composite titanium nitride (rGO / TiN) ink is 0.978 cm·s -1 , in contrast, the water transport rate of the sample prepared based on rGO-F127 ink is only 0.045 cm·s -1 , and the water transport rate of the former is about 22 times that of the latter. It can be seen that the water transport rate of the material in the water evaporation area is much faster than that of the material in the salt crystallization area.
[0069] Table 1: Water transport rates of different materials.
[0070] .
[0071] As shown in Table 2, the ion transport flux of the sample prepared based on rGO / TiN for sodium chloride (NaCl) with a concentration of 3.5 wt% is as high as 11.59 kg·m -2 ·h -1, while the ion transport flux of the sample prepared based on rGO-F127 for 3.5 wt% NaCl is only 0.18 kg·m -2 ·h -1 . The difference in ion transport flux between the two is about 64 times, confirming that the material in the water evaporation region has higher ion transport performance than that in the salt crystallization region.
[0072] Table 2: Ion transport fluxes of different materials.
[0073] .
[0074] Then, the surface morphology of the capillary layer of the ion separation solar evaporator was characterized. As shown in (a) of Figure 5 and (b) of Figure 5 , the SEM images show that the surface of the capillary layer is very dense.
[0075] Finally, the microscopic morphology of the magnesium-lithium separation nanofiltration membrane of the ion separation solar evaporator was characterized. The magnesium-lithium separation nanofiltration membrane is the core component for the separation of magnesium (Mg 2+ ) and lithium (Li + ) in the ion separation solar evaporator. The magnesium-lithium separation nanofiltration membrane adopts a three-layer composite structure design: a polyethersulfone microfiltration membrane as the substrate, single-walled carbon nanotubes (SWCNTs) as the middle support layer, and polyamide (PA) as the top selective layer. As shown in (a) of Figure 6 and (b) of Figure 6 , the SEM images show that the surface of the PA selective layer has highly dense characteristics, which is beneficial to achieving efficient selective sieving of Mg 2+ and Li + .
[0076] The magnesium-lithium separation performance of the ion separation solar evaporator prepared by the method for preparing an ion separation solar evaporator provided in the embodiments of the present application was tested.
[0077] Actual salt lake water usually has a high Mg 2+ / Li + ratio. Therefore, the ion separation solar evaporator was used to treat brine with a high Mg 2 + / Li + ratio to test its magnesium-lithium separation performance. As shown in Table 3, at a light intensity of 1 kW·m -2 , the separation factors of the ion separation solar evaporator for brines with Mg 2+ / Li + ratios of 10, 20, 40, 60, and 80 and a concentration of 20 g·L -1 are 7.50, 9.64, 12.56, 17.40, and 21.68 respectively, indicating that the ion separation solar evaporator has high separation performance for high Mg2+ / Li + has excellent separation performance compared to brine. Its treatment of Mg 2+ / Li + ratios for brines of 10, 20, 40, 60, and 80 are such that the Li + fluxes are 0.112 g·m -2 ·h -1 , 0.092 g·m -2 ·h -1 , 0.049 g·m -2 ·h -1 , 0.017 g·m -2 ·h -1 , and 0.012 g·m -2 ·h -1 . The reason for the decrease in Li + flux is due to the decrease in Li + content in the brine.
[0078] Table 3: Separation factors and Li 2+ / Li + fluxes of the ion separation solar evaporator for Mg + brines.
[0079] .
[0080] Actual salt lake water, in addition to having a high Mg 2+ / Li + ratio, also has an extremely high salt concentration. Therefore, the magnesium-lithium separation performance of the ion separation solar evaporator for treating high-concentration brine was further tested. As shown in Table 4, when the brine concentrations are 20 g·L -1 , 40 g·L -1 , 60 g·L -1 , 80 g·L -1 , and 100 g·L -1 (Mg 2+ / Li + ratio is 10), the separation factors of the ion separation solar evaporator are 7.50, 6.74, 8.04, 8.08, and 6.20 respectively. And the Li + flux of the ion separation solar evaporator shows an upward trend with the increase in brine concentration, being 0.112 g·m -2 ·h -1 , 0.182 g·m -2 ·h -1 , 0.300 g·m -2 ·h -1 , 0.342 g·m -2 ·h -1 , and 0.486 g·m -2·h -1 , which is mainly attributed to the increase in the concentration of Li in the solution, fully demonstrating the ability of the ion separation solar evaporator to treat high-concentration brine. +
[0081] Table 4: Separation factors and Li + flux of the ion separation solar evaporator for brines with different concentrations.
[0082] .
[0083] In addition, to evaluate the adaptability of the ion separation solar evaporator to different light intensities, its magnesium-lithium separation performance for brine with a concentration of 20 g·L -1 and a Mg 2+ / Li + ratio of 10 was tested under different light intensities. As shown in Table 5, the ion separation solar evaporator maintained high separation factors of 7.50, 10.30, 11.14, and 8.73 at light intensities of 1 kW·m -2 , 5 kW·m -2 , 10 kW·m -2 and 15 kW·m -2 , respectively. With the increase in light intensity, the Li + flux of the ion separation solar evaporator continued to increase, and its Li + fluxes were 0.112 g·m -2 ·h -1 , 0.144 g·m -2 ·h -1 , 0.186 g·m -2 ·h -1 and 0.309 g·m -2 ·h -1 , respectively. The increase in Li + flux is mainly due to the increase in evaporation rate, which enhances the driving force for ion transport, thereby driving more Li + to pass through the ion separation layer, fully demonstrating the stability of the ion separation solar evaporator under different light intensities.
[0084] Table 5: Separation factors and Li + flux of the ion separation solar evaporator for brines with different concentrations.
[0085] .
[0086] Explore the magnesium-lithium separation mechanism of the ion separation solar evaporator prepared by the method for preparing an ion separation solar evaporator provided in the embodiments of the present application.
[0087] To explore the magnesium-lithium separation mechanism of the ion-separation solar evaporator, a comparative experiment was designed to study the role of the ion-separation layer. Under the light intensity of 1 kW·m -2 , the Mg 2+ / Li + separation performance of the solar evaporator with and without the ion-separation layer was tested respectively for the brine with a Mg -1 / Li 2+ ratio of 1 and a concentration of 20 g·L + . The separation factor of the solar evaporator without the ion-separation layer was only 1, that is, there was no separation effect on Mg 2+ and Li + . However, the solar evaporator with the ion-separation layer achieved a significant magnesium-lithium separation effect due to the selective sieving effect of the ion-separation layer, and the separation factor reached 7.5. Compared with the solar evaporator without the ion-separation layer, the separation performance was improved by 650%. In the solar evaporator with the ion-separation layer, Li + in the evaporating water body could pass through the ion-separation layer to reach the evaporation interface, while Mg 2+ was effectively intercepted. In the solar evaporator without the ion-separation layer, Mg 2+ and Li + in the evaporating water body could be transmitted to the evaporation interface without hindrance, indicating the importance of the ion-separation layer for magnesium-lithium separation.
[0088] To further explore the reason why the ion-separation solar evaporator can overcome the high osmotic pressure to directly separate magnesium and lithium from concentrated brine, the role of the capillary layer in the ion-separation process was mainly studied. When treating the brine with a Mg 2+ / Li + ratio of 1 and a concentration of 20 g·L -1 , the Li + flux of the solar evaporator without the capillary layer was only 0.051 g·m -2 ·h -1 . However, the solar evaporator with the capillary layer showed excellent Li + transmission performance, and its Li + flux was as high as 0.112 g·m -2 ·h -1 . Compared with the solar evaporator without the capillary layer, Li +The flux has increased by 120%. In a solar evaporator with a capillary layer, the capillary force provided by the capillary layer acts synergistically with evaporation-driven ion migration, which can effectively overcome the obstacle of high osmotic pressure, thereby greatly improving the ion transport rate. In contrast, in a solar evaporator without a capillary layer, there is only a single ion transport driving force brought by the evaporation process, which is difficult to effectively overcome the high osmotic pressure, resulting in slow ion transport, indicating that the capillary layer plays an indispensable role in achieving efficient solar-driven ion separation.
[0089] The magnesium-lithium separation performance of the ion separation solar evaporator prepared by the ion separation solar evaporator preparation method provided in the embodiments of the present application was tested on simulated salt lake water.
[0090] To verify the application potential of the ion separation solar evaporator in the treatment of salt lake brine, the magnesium-lithium separation test was carried out on high-concentration simulated salt lake water. The Mg 2+ / Li + ratio of the simulated salt lake water is 35.17, and the total concentration is 280.76 g·L -1 . Under the light intensity of 15 kW·m -2 , the magnesium-lithium separation test was carried out for 10 h using the ion separation solar evaporator. As shown in Table 6, the evaporator exhibits excellent separation performance, and the Li + content in the harvested product increases while the Mg 2+ content decreases significantly. In addition, as Figure 7 shown, the ion separation solar evaporator can directly realize the crystallization recovery of lithium salts in the salt crystallization area, and its salt production rate is 0.15 g·m -2 ·h -1 . It can be seen that the ion separation solar evaporator can effectively separate magnesium and lithium from high-concentration simulated salt lake water, fully demonstrating the great application value of this technology in the field of salt lake lithium resource development.
[0091] Table 6: Ion contents of simulated salt lake water before and after magnesium-lithium separation.
[0092] .
[0093] The embodiments of the present application provide an application of an ion separation solar evaporator prepared by an ion separation solar evaporator or an ion separation solar evaporator preparation method in any embodiment of the present application in lithium extraction from salt lakes or ion separation.
[0094] The lithium-ion separation solar evaporator provided by any embodiment of the present application can directly extract lithium from high-concentration salt lake water without pretreatment. Under light conditions, through the synergistic effect of the capillary force provided by the capillary layer and the evaporation-driven ion migration, the obstacle of high osmotic pressure is effectively overcome, enabling monovalent ions such as lithium ions in the high-concentration salt lake water to pass through the ion separation layer, while blocking competitive ions such as magnesium ions, for the extraction of lithium resources.
[0095] An embodiment of the present application provides a method for extracting lithium from a salt lake. The lithium-ion separation solar evaporator prepared by the lithium-ion separation solar evaporator or the preparation method of the lithium-ion separation solar evaporator in any embodiment of the present application is placed in the salt lake water, and ions are selectively passed through the ion separation layer for lithium resource extraction.
[0096] Specifically, through the synergistic effect of the evaporation drive in the water evaporation area and the capillary force of the capillary layer, lithium ions in the salt lake water pass through the ion separation layer for lithium extraction from the salt lake.
[0097] The above are only the preferred embodiments of the present application. It should be noted that for those of ordinary skill in the art, without departing from the technical principle of the present application, several improvements and deformations can be made, and these improvements and deformations should also be regarded as the protection scope of the present application.
Claims
1. An ion separation solar evaporator, characterized in that: It includes a transmission channel, an ion separation layer, a capillary layer and a water evaporation zone stacked in sequence, and the water evaporation zone is surrounded by a salt crystallization zone; wherein the transmission channel is made of a two-dimensional layered material, the water evaporation zone is made of a two-dimensional layered material composite surface plasmon material, the salt crystallization zone is made of a two-dimensional layered material composite rheology regulator, the capillary layer is made of a hydrogel, and the ion separation layer adopts an ion separation nanofiltration membrane.
2. The ion separation solar evaporator according to claim 1, characterized in that: The transmission channel is made of reduced graphene oxide, the water evaporation zone is made of reduced graphene oxide composite titanium nitride, the salt crystallization zone is made of reduced graphene oxide composite poloxamer F127, the capillary layer is made of polyvinyl alcohol hydrogel, and the ion separation layer uses a magnesium-lithium separation nanofiltration membrane.
3. The ion separation solar evaporator according to claim 1, characterized in that: The transmission channel is a grid-shaped transmission channel, and the water evaporation zone is a grid-shaped water evaporation zone.
4. A method for preparing an ion separation solar evaporator, characterized in that: include: Prepare two-dimensional layered material ink, two-dimensional layered material composite surface plasmon material ink and two-dimensional layered material composite rheology regulator ink; The transmission channel is 3D printed using two-dimensional layered material ink, the water evaporation area is 3D printed using two-dimensional layered material composite surface plasmon material ink, and the salt crystallization area is 3D printed using two-dimensional layered material composite rheology modifier ink; preparing a hydrogel, and using the hydrogel to prepare a capillary layer; preparing an ion separation nanofiltration membrane, and using the ion separation nanofiltration membrane as an ion separation layer; The ion separation layer, the capillary layer and the water evaporation zone are placed on the transmission channel in sequence, and the salt crystallization zone is surrounded around the water evaporation zone to obtain an ion separation solar evaporator.
5. The method for preparing an ion separation solar evaporator according to claim 4, characterized in that: The two-dimensional layered material ink is reduced graphene oxide ink, the two-dimensional layered material composite surface plasmon material ink is reduced graphene oxide composite titanium nitride ink, and the two-dimensional layered material composite rheology regulator ink is reduced graphene oxide composite poloxamer F127 ink; The preparation of reduced graphene oxide ink, reduced graphene oxide composite titanium nitride ink and reduced graphene oxide composite poloxamer F127 ink comprises: The graphite sheet is stirred in a mixed acid of nitric acid and sulfuric acid, diluted, filtered and dried, and then heat-treated to obtain a heat-treated product; The heat-treated product is reacted with sulfuric acid, phosphorus pentoxide and potassium persulfate, and after washing and drying, an intermediate product is obtained; The intermediate product is reacted with sulfuric acid and potassium permanganate, and the residual potassium permanganate is reduced. After centrifugal washing, water is added to obtain a graphene oxide aqueous solution; adding an ascorbic acid solution to a graphene oxide aqueous solution for reaction, and filtering the solution after the reaction to obtain reduced graphene oxide ink; Adding titanium nitride nanoparticles into reduced graphene oxide ink to obtain reduced graphene oxide composite titanium nitride ink; The reduced graphene oxide ink is mixed with a poloxamer F127 aqueous solution to obtain a reduced graphene oxide composite poloxamer F127 ink.
6. The method for preparing an ion separation solar evaporator according to claim 4, characterized in that: Using two-dimensional layered material ink to 3D print the transmission channel, using two-dimensional layered material composite surface plasmon material ink to 3D print the water evaporation area, and using two-dimensional layered material composite rheology modifier ink to 3D print the salt crystallization area include: The 3D printed transmission channel, water evaporation area and salt crystallization area are freeze-set, vacuum-dried, annealed and treated with oxygen plasma; Wherein, the transmission channel is a grid-shaped transmission channel, and the water evaporation zone is a grid-shaped water evaporation zone; The inks are mixed evenly when used.
7. The method for preparing an ion separation solar evaporator according to claim 4, characterized in that: The hydrogel is polyvinyl alcohol hydrogel; The method of preparing a polyvinyl alcohol hydrogel and using the polyvinyl alcohol hydrogel to prepare a capillary layer comprises: uniformly mixing the polyvinyl alcohol aqueous solution and the glutaraldehyde solution to obtain a mixed solution; Adding hydrochloric acid solution to the mixed solution to initiate a cross-linking reaction and perform gelation to obtain a polyvinyl alcohol hydrogel; removing unreacted impurities in the polyvinyl alcohol hydrogel to obtain pure polyvinyl alcohol hydrogel; The pure polyvinyl alcohol hydrogel was subjected to freeze-thaw treatment and dried to obtain the capillary layer.
8. The method for preparing an ion separation solar evaporator according to claim 4, characterized in that: The ion separation nanofiltration membrane is a magnesium-lithium separation nanofiltration membrane; The preparation of magnesium-lithium separation nanofiltration membrane includes: Dispersing single-walled carbon nanotubes and sodium dodecyl sulfate in deionized water, and after centrifugal purification, modifying with dopamine hydrochloride, and adding tris(hydroxymethylaminomethane) buffer solution to react, to obtain a dopamine hydrochloride / single-walled carbon nanotube dispersion; The dopamine hydrochloride / single-walled carbon nanotube dispersion is filtered onto a polyethersulfone membrane to form a base membrane, which is then dried and sequentially immersed in a piperazine aqueous solution containing sodium dodecyl sulfate and a trimesoyl chloride n-hexane solution for interfacial polymerization. After being rinsed with n-hexane and heat treated, a magnesium-lithium separation nanofiltration membrane is obtained.
9. Use of the ion separation solar evaporator according to any one of claims 1 to 3 or the ion separation solar evaporator prepared by the preparation method of the ion separation solar evaporator according to any one of claims 4 to 8 in extracting lithium from salt lakes.
10. A method for extracting lithium from a salt lake, characterized in that: The ion separation solar evaporator as claimed in any one of claims 1 to 3 or the ion separation solar evaporator prepared by the preparation method of the ion separation solar evaporator as claimed in any one of claims 4 to 8 is placed in salt lake water to allow ions to selectively pass through the ion separation layer to extract lithium resources.
Citation Information
Patent Citations
Preparation method of polyamide composite nanofiltration membrane based on viscous polyamine aqueous solution
CN107649008A
PVA hydrogel-based photo-thermal evaporation material and preparation and application thereof
CN111171340A
Ion separation device, method and application
CN115353247A
Preparation method and application of thin film nano composite film with polydopamine coated aminated multi-walled carbon nanotube as middle layer
CN116392984A
Porous carbon hydrogels for efficient solar interface evaporation
CN116712939A
Cited By
Crown ether modified positively charged polyamide / carbon nanotube nanofiltration membrane as well as preparation method and application thereof
CN122273334A
A method for preparing a nanocomposite membrane, the nanocomposite membrane and its application.
CN122558300A
